2020
DOI: 10.1002/em.22372
|View full text |Cite
|
Sign up to set email alerts
|

Thirdhand smoke exposure causes replication stress and impaired transcription in human lung cells

Abstract: Thirdhand cigarette smoke (THS) is a newly described toxin that lingers in the indoor environment long after cigarettes have been extinguished. Emerging results from both cellular and animal model studies suggest that THS is a potential human health hazard. DNA damage derived from THS exposure could have genotoxic consequences that would lead to development of diseases. However, THS exposure-induced interference with fundamental DNA transactions such as replication and transcription, and the role of DNA repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…We previously reported the formation of DNA strand breaks in THS-exposed human cell lines by the alkaline Comet assay [ 7 ] and γ-H2AX immunofluorescence [ 8 ]. Consistent with these results, we observed that THS exposure increased micronuclei (MN) formation [ 9 ], a marker of genomic instability. These cellular effects are consistent with THS exposure induced adverse effects in vivo [ 10 ].…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…We previously reported the formation of DNA strand breaks in THS-exposed human cell lines by the alkaline Comet assay [ 7 ] and γ-H2AX immunofluorescence [ 8 ]. Consistent with these results, we observed that THS exposure increased micronuclei (MN) formation [ 9 ], a marker of genomic instability. These cellular effects are consistent with THS exposure induced adverse effects in vivo [ 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…For measuring DSBs, immunofluorescence analysis was carried out as described previously [ 9 , 13 ]. For 53BP1 immunostaining, cells grown in 4-well chamber slides (Nunc Lab-Tek) were exposed to NNA (1 and 10 μM) or mock exposure (DMEM only) for 24 h and then washed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese school-aged children exposed to SHS have reduced lung function compared with that of unexposed children (He et al, 2011). An in vitro study shows that THS exposure can impair DNA replication and transcription in human lung cells (Sarker et al, 2020). In addition, low-dose nicotine in tobacco smoke can induced EGFR phosphorylation via nicotine acetylcholine receptor subunit 5 (5-nAChR) and promote lung adenocarcinoma progression (Wang et al, 2020).…”
Section: Ths Exposure On Multiple Organsmentioning
confidence: 99%